2019
DOI: 10.1177/0890334419878119
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Factors Influencing Attitudes to Breastfeeding in Public

Abstract: Background: Negative attitudes toward breastfeeding in public have consistently been identified as a key barrier to breastfeeding continuation. In order to design effective social marketing campaigns to improve public attitude toward breastfeeding in public, it is critical to identify segments of the population who are less likely to support this activity, their underlying reasons, and the medium through which they can be reached. Research aim: The aims were to (a) identify the underlying dimensions that drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…A cross-sectional survey with 7190 UK respondents explored factors influencing attitudes and found that acceptance of breastfeeding in public varied according to gender, age, religion, and parental and breastfeeding status. 11 Age and education as an influence was supported in one American study where lack of comfort was highest with adults with a lower education level and those 65 years and older. 6 The Australian cross sectional series by Meng et al 10 found that women, people older than 44 years, those born outside of Australia and those with lower education levels were more likely to suggest that breastfeeding in public was not acceptable.…”
mentioning
confidence: 94%
“…A cross-sectional survey with 7190 UK respondents explored factors influencing attitudes and found that acceptance of breastfeeding in public varied according to gender, age, religion, and parental and breastfeeding status. 11 Age and education as an influence was supported in one American study where lack of comfort was highest with adults with a lower education level and those 65 years and older. 6 The Australian cross sectional series by Meng et al 10 found that women, people older than 44 years, those born outside of Australia and those with lower education levels were more likely to suggest that breastfeeding in public was not acceptable.…”
mentioning
confidence: 94%
“…Nouer and colleagues [ 16 ] found that American women were more likely than men to report feeling comfortable with mothers breastfeeding in the workplace, but no gender difference was found when asked about breastfeeding in a shopping mall. In the U.K., women reported greater support for public breastfeeding than men did [ 27 ]. However, other studies from Australia and Canada have demonstrated that women are less likely than men to say that breastfeeding in a variety of public locations is acceptable [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Older participants had more favorable attitudes toward breastfeeding than younger participants did, but this was moderated by location: there was no difference in feelings toward the privately breastfeeding woman, but older participants’ feelings toward the publicly breastfeeding woman were less negative than were younger participants’ feelings. In the U.K., relatively high levels of support for public breastfeeding were found among parents in general, as well as among parents whose children were breastfed and whose children were breastfed in public [ 27 ]. Taken together, these results suggest that greater experience with breastfeeding positively influences perceptions of (public) breastfeeding.…”
Section: Introductionmentioning
confidence: 99%
“…Attitudes towards breastfeeding in public have been researched extensively; however, research about attitudes among the general public are often limited to close-ended questions about situational statements ( Morris et al, 2020 ; Russell & Ali, 2017 ). When study participants have been shown photographs of breastfeeding in public or have discussed public breastfeeding in qualitative interviews (beyond agreement with situational statements), the discomfort becomes clear ( Fairbrother & Stanger-Ross, 2010 ; Magnusson et al, 2017 ; Spurles & Babineau, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, public backlash occurred after a woman in the United Kingdom was kicked out of a shop for breastfeeding, however analysis of the public response to the backlash revealed overwhelmingly negative reactions towards breastfeeding, including sexualization of breasts and abusive language (Grant, 2016). Attitudes towards breastfeeding in public have been researched extensively; however, research about attitudes among the general public are often limited to close-ended questions about situational statements (Morris et al, 2020;Russell & Ali, 2017). When study participants have been shown photographs of breastfeeding in public or have discussed public breastfeeding in qualitative interviews (beyond agreement with situational statements), the discomfort becomes clear (Fairbrother & Stanger-Ross, 2010;Magnusson et al, 2017;Spurles & Babineau, 2011).…”
Section: Breastfeeding In Publicmentioning
confidence: 99%